Before Adolf Eichmann: A Kafkian Analysis of the ‘Banality Of Evil’ - Matthew Wester (The Polish Journal of Aesthetics, 2019)
Arendt’s account of Adolf Eichmann as acting only out of banal intentions remains controversial. I supplement our understanding of the “banality of evil” by demonstrating that Arendt also meant it to describe a factual social arrangement characterized by aform of false consciousness. I apply an original interpretation of Kafka’s The Trial to Eichmann in Jerusalem, and I show that Eichmann’s trial was “before” him in the same way as the Kafkian man from the country is “before” the Law.